THE STEEL DRUMS OF KIM LOY WONG. An instruction book by PETE SEEGER. Oak Publications, Inc., 121 W. 47th. St., New York, N.Y., U.S.A. 1961, pp. 40, $2.95. To accompany Folkways records FI-8367 and FS-3834, and the film, “Music from Oil Drums” - Tracey, Andrew (International Library of African Music, 1961)
pages: 107
Keywords: African Music